Differential induction of polar and non‐polar metabolism during wound‐induced suberization in potato (Solanum tuberosum L.) tubers. (7th February 2018) - Woolfson, Kathlyn N.; Haggitt, Meghan L.; Zhang, Yanni; Kachura, Alexandra; Bjelica, Anica; Rey Rincon, M. Alejandra; Kaberi, Karina M.; Bernards, Mark A.
Summary: Wound‐induced suberin deposition involves the temporal and spatial coordination of phenolic and fatty acid metabolism. Phenolic metabolism leads to both soluble metabolites that accumulate as defense compounds as well as hydroxycinnamoyl derivatives that form the basis of the poly(phenolic) domain found in suberized tissue. Fatty acid metabolism involves the biosynthesis of very‐long‐chain fatty acids, 1‐alkanols, ω‐hydroxy fatty acids and α, ω‐dioic acids that form a poly(aliphatic) domain, commonly referred to as suberin. Using the abscisic acid (ABA) biosynthesis inhibitor fluridone (FD), we reduced wound‐induced de novo biosynthesis of ABA in potato tubers, and measured the impact on the expression of genes involved in phenolic metabolism ( StPAL1, StC4H, StCCR, StTHT ), aliphatic metabolism ( StCYP86A33, StCYP86B12, StFAR3, StKCS6 ), metabolism linking phenolics and aliphatics ( StFHT ) or acyl chains and glycerol ( StGPAT5, StGPAT6 ), and in the delivery of aliphatic monomers to the site of suberization ( StABCG1 ). In FD‐treated tissue, both aliphatic gene expression and accumulation of aliphatic suberin monomers were delayed. Exogenous ABA restored normal aliphatic suberin deposition in FD‐treated tissue, and enhanced aliphatic gene expression and poly(aliphatic) domain deposition when applied alone. By contrast, phenolic metabolism genes were not affected by FD treatment, while FD + ABA and ABA treatments slightly enhanced the accumulation of polar metabolites. These data support a role for ABA in the differential induction of phenolic and aliphatic metabolism during wound‐induced suberization in potato. Significance Statement: ABA is involved in the differential induction of phenolic and aliphatic metabolism during wound‐induced suberization in potato.